The Influence Of Competency, Compensation, And Work Discipline On The Performance Of Makassar City Revenue Service Employees - Muh. Arif; Riska Eka Putri Bachtiar (STIE Amkop Makassar, 2024)
This research aims to determine the influence of competency and work discipline on the performance of Makassar City Revenue Service employees.